Hospital Course and Outcome of Patients Admitted to Critical Care Unit with Cerebral Venous Sinus Thrombosis - KC, Bidur (Nepal Journal of Neuroscience, 2022)
Introduction: Cerebral venous sinus thrombosis (CVST) is a potentially serious neurological condition. Yet, non-specific clinical and radiological features of cerebral venous sinus thrombosis, making it delay in the diagnosis and subsequent management. This study aims to find the hospital course and outcome of patients. Methods: A descriptive cross-sectional study was done in patients with diagnosis of cerebral venous sinus thrombosis confirmed by computed tomography or by magnetic resonance imaging with magnetic resonance venography. Demography, clinical features, hospital course and outcome at hospital discharge were recorded and analysed. Results: A total of nine patients included in the study. Mean age of patient was 33.22 ± 9.24 years with male to female ratio of 1:2. Headache was the most common presenting symptom found in eight patients. GCS at admission of all of the patients were 15 except for 2 patients. Surgical intervention was required in two patients. Good outcome with mRS score of 0 was found in eight patients at hospital discharge. No mortality was observed in this study. Conclusions: Favorable outcome was found in most of the patients at hospital discharge. Nonetheless, complications can occur during the hospital course which might require surgical intervention.